MANUFACTURING TECHNIQUE OF METAL CERAMIC RESTORATION WITH IMPLANT-ABUTMENT AT GINGIVAL RESORPTION CASE - Paramarta, Galih; Inayati, Eny (Journal of Vocational Health Studies, 2019)
Background: The low levels of patient satisfaction and confidence in the restoration of the gingival resorption results in impaired quality of life in both functional and psychosocial aspects. It is necessary to manufacture a dental restoration to restore the mastication, phonetic, and aesthetic functions associated with soft tissue repair. Manufacture of gingiva ceramic restorations which are believed to be an alternative to restore the aesthetic function and harmonization of the patient's teeth. In terms of manufacturing techniques, this restoration has a level of difficulty in achieving a balance between "White aesthetic” and "aesthetic pink”. Purpose: This study aims to provide knowledge to the reader of Manufacturing Technique of Metal Ceramic Restoration with Implant-Abutment at Gingival Resorption Case. Review: Gingiva ceramic restorations can be used to create esthetic implant-supported restorations when bone and gingival tissues are deficient and surgical replacement of such tissues is not possible. Dental technicians should be able to analyze the three-dimensional shapes of gingival anatomy, color, texture, smile components, the balance of the "pink aesthetic” and "white aesthetic”. Conclusion: Manufacturing Technique of Metal Ceramic Restoration with Implant-Abutment at Gingival Resorption Case including the manufacture of metal coping, oxidation, application of opaque coating, application of the first "white aesthetic” ceramics (Opaque Dentine, Dentine, Enamel and transpa on crown coping restorations), Application of opaque gingiva layer, gingival ceramics build-up "pink aesthetics”, first firing, followed by correction build-up, and second firing, and ends with the glazing process.